2021
DOI: 10.3389/fbioe.2021.662381
|View full text |Cite
|
Sign up to set email alerts
|

3D Printed Poly(ε-Caprolactone)/Meniscus Extracellular Matrix Composite Scaffold Functionalized With Kartogenin-Releasing PLGA Microspheres for Meniscus Tissue Engineering

Abstract: Meniscus tissue engineering (MTE) aims to fabricate ideal scaffolds to stimulate the microenvironment for recreating the damaged meniscal tissue. Indeed, favorable mechanical properties, suitable biocompatibility, and inherent chondrogenic capability are crucial in MTE. In this study, we present a composite scaffold by 3D printing a poly(ε-caprolactone) (PCL) scaffold as backbone, followed by injection with the meniscus extracellular matrix (MECM), and modification with kartogenin (KGN)-loaded poly(lactic-co-g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 36 publications
4
37
0
Order By: Relevance
“…The study was approved by the Ethical Committee of PLA. Isolation and culture of SMSCs were performed according to a previous method [ 33 , 34 ]. In general, articular synovial tissue was obtained from the knee joints of male New Zealand rabbits (1 month old, 500–800 g) on a sterile bench.…”
Section: Methodsmentioning
confidence: 99%
“…The study was approved by the Ethical Committee of PLA. Isolation and culture of SMSCs were performed according to a previous method [ 33 , 34 ]. In general, articular synovial tissue was obtained from the knee joints of male New Zealand rabbits (1 month old, 500–800 g) on a sterile bench.…”
Section: Methodsmentioning
confidence: 99%
“…A study by Tarafder et al (2018) reported that the controlled applications of CTGF and TGF-β3 can induce seamless healing of avascular meniscus tears by inducing the recruitment and step-wise differentiation of SMSCs. Additionally, chemical and physical conditions have also been further investigated, with promising results in PCL electrospinning technology, magnesium ions, 3D printing-based biomimetic, and composite tissue-engineered meniscus scaffold ( Shimomura et al, 2019 ; Zhang et al, 2019 ; Li et al, 2020 ; Li et al, 2021 ). To ensure clinical efficacy, the proper transport of SMSCs from the processing facility to the clinic is important.…”
Section: Stem Cell Therapiesmentioning
confidence: 99%
“…In another study, Li et al . [ 109 ] fabricated an ingenious scaffold as a drug and stem cell delivery system, which composed of 3D-printed PCL, meniscus extracellular matrix (MECM), and KGN-loaded poly(lactic-co-glycolic) acid (PLGA) microsphere (Fig. 4 ).…”
Section: Preclinical Advances In Scaffold-based Stem Cell Therapymentioning
confidence: 99%